Performance Evaluation of Doubly-Fed Induction Generator Using Combined Vector Control and Direct Power Control Method - Khalil Valipour; Reza Najafi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper presents the performance evaluation of Doubly-Fed Induction Generator Using Combined Vector Control and Direct Power Control Method. Combined vector and direct power control (CVDPC) is used for the rotor side converter (RSC) of double-fed induction generators (DFIGs). The control system is according a direct current control by selecting suitable voltage vectors from a switching table. Actually, the proposed CVDPC encompass the benefits of vector control (VC) and direct power control (DPC) in a compact control system. Its benefits compare with VC contains rapid dynamic response, Stability against the machine parameters Changes, less computation, and naive implementation. On the other hand, it has benefits compared with DPC, contains less harmonic distortion and lower power ripple. This technique is to improve the dynamic performance of the DFIG driven by the wind-energy conversion system.